To solve this equation, we can simplify both sides and equate the exponents:
On the left side of the equation:
k^5 ⋅ k^2/k^x = k^(5+2-x) = k^(7-x)
On the right side of the equation:
(k^2)^(-2) = k^(2*(-2)) = k^(-4)
Therefore, the equation can be rewritten as follows:
k^(7-x) = k^(-4)
To satisfy this equation, the exponents on both sides must be equal:
7 - x = -4
Adding x to both sides, we get:
7 = x - 4
Adding 4 to both sides, we get:
11 = x
Therefore, the missing exponent that would make the equation true is x = 11.
What is the missing exponent that would make this equation true? k^5 ⋅ k^2/k^x = (k^2)^−2
1 answer